2022
DOI: 10.1149/1945-7111/ac4542
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in MacMullin Number of Li-Ion Battery Electrodes Studied by Means of an Aperture Probe

Abstract: Heterogeneity of MacMullin number within battery electrodes is a key metric affecting cell performance. To characterize this heterogeneity, an aperture probe was developed. This probe, coupled with a newly developed transmission-line model, allows for measurements of tortuosity, represented by the MacMullin number, on millimeter length scales. Local MacMullin number values of seven electrodes were measured, and the ionic resistance profiles of these electrodes are given through contour maps of the MacMullin nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 41 publications
2
12
0
Order By: Relevance
“…In the limit that σ ? k, which is consistent with experimental data of graphite anodes including the EnPower anode, 25,33 the electronic potential in the electrode becomes effectively constant (φ 1 = 0) for both upper and lower layers. Given that the ionic potential is independent of the azimuth, the model only needs to be solved in 2 dimensions, r and z.…”
Section: Model Developmentsupporting
confidence: 89%
See 3 more Smart Citations
“…In the limit that σ ? k, which is consistent with experimental data of graphite anodes including the EnPower anode, 25,33 the electronic potential in the electrode becomes effectively constant (φ 1 = 0) for both upper and lower layers. Given that the ionic potential is independent of the azimuth, the model only needs to be solved in 2 dimensions, r and z.…”
Section: Model Developmentsupporting
confidence: 89%
“…To distinguish the two types of 2D transmission-line models, we name the 2D transmission-line model developed in previous publication 33 the single-layer 2D transmission-line model (singlelayer 2D TLM), and we name the 2D transmission-line model with step-function configuration the dual-layer 2D transmission-line model (dual-layer 2D TLM). The same notation is also applied to 1D transmission-line models.…”
Section: Model Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The pseudo‐3D (P3D) model is developed in COMSOL multiphysics, with parameters and equations reported in the Supporting Information. To induce in‐plane heterogenous utilization, the electrolyte tortuosity is assumed to vary in accordance with work from Liu et al [ 28 ] and details are shown in the Supporting Information. This heterogeneous tortuosity is implemented in both the cathode and anode domains.…”
Section: Methodsmentioning
confidence: 99%